Proses Berpikir Siswa dengan Gaya Kognitif Reflektif dalam Memecahkan Masalah Matematika Generalisasi Pola - Silfia Hayuningrat; Tomi Listiawan (Jurnal Elemen, 2018)
This research was conducted to explain the thinking process of students in solving mathematical problems of pattern generalization based on Polya measurement in terms of Reflective cognitive style. This research is a qualitative descriptive research with class X class IPA 1 SMA N Kalidawir consisting of 25 students. Selection of research subjects using cognitive style instrument that is Matching Familiar Figures Tests developed Warli, the test was given to all students class X IPA 1 to determine the subject of research. The data collection in this research uses generalized pattern test with think aloud method, interview, and triangulation technique to check the validity of the data. Data were analyzed using the concepts from Miles and Huberman: data reduction, data presentation, and conclusions. The results of this study indicate that the process of thinking of the Reflective subject at the stage of understanding the problem experienced the process of dominant assimilation thinking to arithmetic, the problem planning phase experienced the process of assimilation thinking, accommodation and dominant abstraction to algebra, accommodation and abstraction, assimilation of accommodation and the dominant abstraction into algebra, and at the stage of re-experiencing the process of assimilation thinking and the dominant abstraction into algebra.